2013
DOI: 10.1111/vox.12089
|View full text |Cite
|
Sign up to set email alerts
|

Residual aggregates in platelet products: what do we know?

Abstract: Despite the fact that PLT aggregates occur in PLT products, published data on this topic remain scant. Considering the concern of clinicians about this phenomenon, more studies are needed which should focus on the possible clinical impact of such aggregates and precautions to avoid PLT aggregate formation in PLT products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 57 publications
1
17
1
1
Order By: Relevance
“…The primary interaction between platelets and the damaged vessel wall is highly dependent on the prevailing fluid shear forces and strengthens in proportion to the impacting drag . Apheresis involves fluid aspiration and centrifugation of blood or its components, and this process equally evokes fluid shear and drag forces that may facilitate platelet–platelet binding through GPIbα and sheared soluble plasma VWF . Furthermore, our previous work on this topic indicated that certain donors are more likely to routinely donate concentrates with PA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary interaction between platelets and the damaged vessel wall is highly dependent on the prevailing fluid shear forces and strengthens in proportion to the impacting drag . Apheresis involves fluid aspiration and centrifugation of blood or its components, and this process equally evokes fluid shear and drag forces that may facilitate platelet–platelet binding through GPIbα and sheared soluble plasma VWF . Furthermore, our previous work on this topic indicated that certain donors are more likely to routinely donate concentrates with PA .…”
Section: Discussionmentioning
confidence: 99%
“…Apheresis has specific advantages and disadvantages compared to other modalities of platelet concentrate production . One practical problem in apheresis is the presence of platelet aggregates in the final product . These structures are poorly defined but manifest as macroscopic hyaline structures that are clearly visible to the naked eye, with or without backlighting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apheresis procedures may cause platelet aggregation. These generally dissipate, but some persist throughout the entire storage period . Products with persisting aggregates (PA) may be quarantined, destroyed or distributed in which case an evaluation procedure can be used as a guideline .…”
Section: Introductionmentioning
confidence: 99%
“…A practical consequence of the higher platelet concentration in PA donor's whole blood is the larger products these donors provide, but it is unclear whether collection of smaller products from such donors would help driving back PA incidence. To mitigate PA incidence, previous reports have suggested to increase the anticoagulant to inlet ratio, but additional research is required to confirm utility and investigate the consequences for donor and operators . With the adoption of Intercept pathogen inactivation, PA have disappeared in our blood institution.…”
Section: Introductionmentioning
confidence: 99%